Pengaruh Kelengkapan Kesehatan dan Keselamatan Kerja (K3) Terhadap Kecelakaan Kerja di PDAM Tirta Bulian Tebing Tinggi - Muda, Riskilan; Munthe, Sirmas; Delvika, Yuana (Universitas Medan Area, 2022)
PDAM Tirta Bulian Tebing Tinggi is a company run in the processing of clean water by the Regional Drinking Water Company (PDAM). In the last 2 years, there has been an increase in the number of accidents on the production floor. This result was a major problem that human resources are the most important asset for the company so that it needs to be protected by the OHS program, where the company is based on the achievement level of the implementation OHS management program. Measurement of the OHS management program achievement level was carried out by distributing questionnaires to production floor employees to obtain the achievement level of the implementation OHS management program at PDAM Tirta Bulian Tebing Tinggi. Then, the success rate measurement of the OHS management program was carried out by conducting an OHSMS audit based on the Government Regulations Republic of Indonesia number 50 in 2012 towards the OHS management program that has been owned by PDAM Tirta Bulian Tebing Tinggi. Furthermore, the success rate of implementing the OHS program was at 54.21%, or the red category where violations of laws and regulations could be subject to legal action. The measurement results showed a lack of company attention to occupational safety and health for employees and company assets. Thus based on the measurement results, the company must immediately improve the OHSMS based on the government’s rules.